2017
DOI: 10.18632/oncotarget.19394
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin, relocated to the front ends, can control the migration directionality of colorectal cancer cells

Abstract: Directional migration is a cost-effective movement allowing invasion and metastatic spread of cancer cells. Although migration related to cytoskeletal assembly and microenvironmental chemotaxis has been elucidated, little is known about interaction between extracellular and intracellular molecules for controlling the migrational directionality. A polarized expression of prohibitin (PHB) in the front ends of CRC cells favors metastasis and is correlated with poor prognosis for 545 CRC patients. A high level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The nude mouse model further revealed that CRC pulmonary metastases were associated with VEGF stimulation, NRP1 transfer, and Cdc42 activation, which corroborated the findings of our previous study and indicated that the directionality of protrusion formation and the high VEGF levels in interstitial tissues were consistent with metastatic production 3 . Cdc42 activation and relocation are at the core of the cell front assembly, which involves filopodia and invadopodia.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The nude mouse model further revealed that CRC pulmonary metastases were associated with VEGF stimulation, NRP1 transfer, and Cdc42 activation, which corroborated the findings of our previous study and indicated that the directionality of protrusion formation and the high VEGF levels in interstitial tissues were consistent with metastatic production 3 . Cdc42 activation and relocation are at the core of the cell front assembly, which involves filopodia and invadopodia.…”
Section: Discussionsupporting
confidence: 89%
“…Both VEGF and activated Cdc42 stimulate LIM domain kinase 2 (LIMK2) to phosphorylate and activate cofilin, which, in turn, regulates actin dynamics 16,17 . Because it has been demonstrated that VEGF controls the directionality of migrating CRC cells 3 , we propose that VEGF/ NRP1 participates in the assembly of the cell front, such as the formation of filopodia and invadopodia and that Cdc42 might be involved in migration and invasion in response to VEGF stimulation, possibly uncovering a unique portrait of the molecular-subcellular frame.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In primary tumor tissue samples, however, PHB was significantly but modestly overexpressed in patients with relapsed Wilms' tumor as compared with those who had cured Wilms' tumor and normal kidney tissue (Figure 3 and Supplemental Figure 5). Thus, urine PHB elevation may be due to increased Wilms' tumor cell invasion and PHB release into renal tubules, as suggested by the increased invasiveness of colorectal and lung carcinomas with PHB overexpression (46)(47)(48). This possibility is further supported by the relatively higher frequency of abdominal Wilms' tumor relapse in patients with elevated urine PHB (Figure 2E).…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, cancer cells expressing high levels of PHB show an enhanced capacity for migration and invasion, cellular qualities associated with metastatic disease (12,13). Notably, it was recently reported that PHB is required for dictating the directionality of invasive colorectal cancer cells (14). Although PHB has been extensively characterized in adult tumors, its role in pediatric cancers remains undefined.…”
Section: Introductionmentioning
confidence: 99%